Mathematics
laurenbaileyx
10

What is the following product? (x√7-3√8)(x√7-3√8) A. 7x^2+72 B. 7x^2-12x√14+72 C. 7x^2-12x√14-72 D. 7x^2-72

+1
(1) Answers
YolandeSehl667

hello :  by identity : (a-b)² = a² +b² -2ab (x√7-3√8)(x√7-3√8) = (x√7-3√8)² = (x√7)²+(3√8)² -2(x√7)(3√8)                                                     =7x²+72 -6x√56                                                      = 7x²+72-6x√(14×4)                                                      = 7x²+72-12x√(14).because  :√(14×4)=2√14 Answer B

Add answer